SYSTEM INFORMATION DEVELOPMENT PLAN OF TUITION PAYMENT BY SDLC WATERFALL METHOD - Nurasiah, Nurasiah (Universitas Gunadarma, 2014)
Information and Communication Technology utilization on academic administration service in college is now a need. It is no longer a prestige or a modern college management lifestyle. The writer conduct an analysis of system information of tuition payment occuring in the college. She develops the system information of the occuring tuition payment by waterfall method and draws a system design described by Unified Modelling Language (UML). The academic integrated and online system can make the system become more efficient and effective so that it produces the more accurate information.Keywords: SDLC, Waterfall, Tuition